Ewing’s sarcoma of fifth metacarpal with lung metastasis in a child: an unusual presentation - Singh, Nidhi N.; Gupta, V.; Singh, Ashutosh K. (International Journal of Contemporary Pediatrics, 2017)
Ewing’s sarcoma is the second most common bone tumour second only to osteosarcoma which represents a family of malignancies of neuroendothelial origin, which are highly aggressive and poorly differentiated. The most frequent sites involved are shaft of long bones such as femur, tibia and flat bones such as pelvis and vertebra. Ewing’s sarcoma of small bones of hands is very rare and distant metastasis with hands as the primary is even rarer. Here we describe the course of a 11-year-old male who presented with ewings sarcoma of fifth metacarpal who presented with lung metastasis without local recurrence of the disease after primary surgery and later succumbed to his illness.